Representations of Women in the Film El regreso (2011) in the Light of the Essay Mujer y cultura (1990) - Solís Lemus, Valeria (2024)
Introduction: The article presents a comparative analysis of the female ties and liberations in two Costa Rican artistic products: the film El regreso (2011), by Hernán Jiménez, and the essay Mujer y cultura (1990), by Carmen Naranjo. Objective: The analysis aims to put the film and the literary text into dialogue, mainly from a gender perspective. Methods: To this end, the text Mujer y cultura is taken as a critical apparatus to analyze the myths raised by Camen Naranjo in her essay and its representation in the film character Amanda. Conclusions: Besides the temporal distance between both texts, what is outlined in one work fits perfectly to analyze the other. Also, the analysis allows us to understand how the representation of women is constructed in Costa Rican cultural products, as well as in society. In this case, through the synthesis of cultural myths in a single film character.